Student's Perception of the Use of YouTube Channel "Learn English with TV Series" to Improve Vocabulary Knowledge - Elfrida Situmorang; Ellis Tamela; Chusnul Chotimah (Akademika, 2024)
Relevance of Digital Media in Learning: Today’s young generation is familiar with online platforms like YouTube. This study can show how digital media can be used effectively to help students learn a foreign language, especially English. This study aimed to determine students' perceptions of the use of YouTube in improving students' vocabulary mastery. The research gap in the problem is the still low mastery of English vocabulary of High School Class XI IPS 2 students so they lack understanding and are less active in learning. Using convenient sampling, the respondents are 10 students of class XI IPS 2 High School Babelan. The method used is the descriptive qualitative method. The instrument used is an interview. The research was conducted for 6 months. The results concluded that the use of the YouTube channel Learn English With TV Series for English learning received positive perceptions from students. It was found to be particularly effective in helping students improve their English vocabulary. These findings suggest several practical implications. For teachers, integrating YouTube videos like this into their lessons can provide engaging and authentic materials that expose students to real-world English usage. Teachers can design activities around these videos, such as vocabulary-building exercises, comprehension tasks, or discussion prompts, to enhance learning outcomes. For students, watching these videos independently can serve as a supplementary resource for practicing listening skills, expanding vocabulary, and understanding cultural references in English. Encouraging students to interact with the content, such as by noting new words or mimicking phrases, can further solidify their learning.